Performance and Safety Evaluation of Gas Burner Using Fluid Structure Interaction (FSI) Study - Sheidu Sumaila O.; Osuagwu Chidiebere F.; Agbadua Afokhainu S; Alutu Ngozi C.; Adebola Etiosa R. (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Performance and safety evaluation of cooking gas burners has been a very important phase of ensuring efficient and safe cooking processes in households and commercial kitchens. Gas burners performance and safety have been studied using the ANSYS Fluent with regards to heat management for three different materials aluminum, stainless steel and brass for 3,600 seconds. Propane that is the major component of Natural gas was used as the fuel and the gauge pressure for 12.5 kg gas cylinder of 18 bar was used with average gas mass flow rate of 0.07 kg/h. From the findings of these studies, it was observed that brass made the best material for cooking gas burner for safety purposes with regards to effective heat managements It was observed that stainless steel has the highest value of 0.010C/s followed by aluminum and brass with least value of 0.00440C/s and 0.000350C/s respectively over the period of 3,600 seconds of investigating the rate of heat transfer from the top of the burner in contact with the burning flame. The heat flux which represents the rate of heat loss to the surrounding for Aluminum, stainless steel and brass are 0.3392W/mm2, 0.3W/mm2 and 0.3403 W/mm2 respectively.
Keywords: ANSYS Fluent; Gas Burners; Aluminum; Safe Cooking